Light induced photovoltaic and pyroelectric effects in ferroelectric BaTiO3 film based Schottky interface for self‐powered and flexible multi‐modal logic gates - Huiyu Dan; Hongyu Li; Lan Xu; Chong Guo; Chris R. Bowen; Ya Yang (InfoMat, 2024)
Abstract Optoelectronic logic gates have emerged as one of the key candidates for the creation of next generation logic devices. However, current optoelectronic logic gates can provide only one or two logic gates, severely limiting their applications. Here we report a self‐powered and mechanically flexible device based on a BaTiO3 ferroelectric film to produce multi‐modal logic gates. By exploiting the photo‐induced photovoltaic and pyroelectric effects of a Schottky junction which is created between BaTiO3 and LaNiO3, the device is able to provide five different optoelectronic logic gates, which can be operated using input lasers of different wavelength (405 or 785 nm). The mode of operation of the logic gate can be switched by controlling the wavelength and intensity of the input laser, where the switching process is both lossless and reversible. A logic gate array was designed to conduct the five logic operations, with 100% accuracy, thereby providing application potential for the Internet of Things, big data, and secure solutions for data processing and transmission.